2014
DOI: 10.1055/s-0034-1376313
|View full text |Cite
|
Sign up to set email alerts
|

The Problem of Preterm Delivery after Laser Surgery

Abstract: Preterm birth after fetoscopic laser surgery for twin-twin transfusion continues to be a major challenge despite improved survival rates. The risk factors for the complications have been identified, which include preterm premature rupture of membranes, cervical length shortening, larger cannula diameter, amnioinfusion, complicated procedure, and severe disease. The interventions to prevent preterm birth such as cervical cerclage for short cervix and collagen plug placement have not been successful. Further und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Mean gestational age at delivery in both groups was approximately 30+4 weeks, which compares to what has been published in the literature and is largely due to complications related to laser (see Table 2) as well as maternal and fetal indications for delivery [16][17][18][19]. We found that DS was significantly diminished by the presence of concomitant sFGR, at the expense of the donor twin.…”
Section: Discussionsupporting
confidence: 57%
“…Mean gestational age at delivery in both groups was approximately 30+4 weeks, which compares to what has been published in the literature and is largely due to complications related to laser (see Table 2) as well as maternal and fetal indications for delivery [16][17][18][19]. We found that DS was significantly diminished by the presence of concomitant sFGR, at the expense of the donor twin.…”
Section: Discussionsupporting
confidence: 57%
“…These studies have included factors such as preoperative cervical length <2.0 cm, preoperative subchorionic hematoma, recipient's MVP 14 cm, incomplete laser surgery, trocar dia-meter, and postoperative chorioamnion membrane separation. 5,6,9,[11][12][13] Our study is the first to examine the effect of trocar insertion location on PPROM and PTB rates. The results of this study indicate that the LUS, especially the lateral regions, is more likely to be associated with PPROM after laser surgery.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 This leaves a fetoscopic defect that persists until delivery, which among other factors, increases the risk of preterm premature rupture of membranes (PPROM) and preterm birth (PTB) after laser surgery. 5,6 The definition of iatrogenic PPROM after laser surgery used in the literature varies, and in a systematic review has been reported to occur at a mean rate of 27%. 7 The mean gestational age (GA) at delivery after laser surgery has been estimated at 32.8 weeks 8 with 8-30% undergoing PTB < 28 weeks depending on the presence or absence of PPROM.…”
mentioning
confidence: 99%
“…Furthermore, a driver of prematurity is PPROM, as the hole in the membrane created by the fetoscopic instruments does not heal, and up to 40% of all FLP will end in PPROM 10–12 . Various tocolytic regimens from magnesium to indomethacin to nifedipine have been evaluated postoperatively, without any particular regimen proven to impact the latency time from surgery to delivery, and much of the work on prevention of PPROM has focused on ways to close the defect created by the fetoscopic entry 13,14 . In one study, the use of an amnioinfusion during FLP was associated with preterm delivery, 15 it has been postulated that the fluid used may contribute to membrane breakdown, 10 and recent presentations have shown that even with a small uterine defect, repeatedly infusing fluid into the amniotic space is associated with high rates of PPROM 16 .…”
Section: Introductionmentioning
confidence: 99%